Can the Ni classification of vessels predict neoplasia? A systematic review and meta‐analysis. (10th June 2017) - Mehlum, Camilla S.; Rosenberg, Tine; Dyrvig, Anne‐Kirstine; Groentved, Aagot Moeller; Kjaergaard, Thomas; Godballe, Christian
Abstract : Objectives: The Ni classification of vascular change from 2011 is well documented for evaluating pharyngeal and laryngeal lesions, primarily focusing on cancer. In the planning of surgery it may be more relevant to differentiate neoplasia from non‐neoplasia. We aimed to evaluate the ability of the Ni classification to predict laryngeal or hypopharyngeal neoplasia and to investigate if a changed cutoff value would support the recent European Laryngological Society (ELS) proposal of perpendicular vascular changes as indicative of neoplasia. Data Sources: PubMed, Embase, Cochrane, and Scopus databases. Review Methods: A systematic review and meta‐analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis statement. We systematically searched for publications from 2011 until 2016. All retrieved studies were reviewed and qualitatively assessed. The pooled sensitivity and specificity of the Ni classification with two different cutoffs were calculated, and bubble and summary receiver operating characteristics plots were created. Results: The combined sensitivity of five studies (n = 687) with Ni type IV‐V defined as test‐positive was 0.89 (95% confidence interval [CI]: 0.76‐0.95), and specificity was 0.82 (95% CI: 0.72‐0.89). The equivalent combined sensitivity of four studies (n = 624) with Ni type V defined as test‐positive was 0.82 (95% CI: 0.75‐0.87), and specificity was 0.93 (95% CI: 0.82‐0.97). Conclusions: The diagnostic accuracy of the Ni classification in predicting neoplasia was high, without significant difference between the two analyzed cutoff values. Implementation of the proposed ELS classification of vascular changes seems reasonable from a clinical perspective, with comparable accuracy. Attention must be drawn to the accompanying risk of exposing patients to unnecessary surgery. Laryngoscope, 128:168–176, 2018